Early body weight loss during concurrent chemo‐radiotherapy for non‐small cell lung cancer. Issue 2 (23rd January 2014) - Op den Kamp, Céline M. H.; De Ruysscher, Dirk K. M.; van den Heuvel, Marieke; Elferink, Meike; Houben, Ruud M. A.; Oberije, Cary J. G.; Bootsma, Gerben P.; Geraedts, Wiel H.; Pitz, Cordula C. M.; Langen, Ramon C.; Wouters, Emiel F. M.; Schols, Annemie M. W. J.; et al.
Abstract : Background and purpose: Radiation‐esophagitis and weight loss are fre.uently observed toxicities in patients treated with concurrent chemo‐radiotherapy (CT‐RT) for non‐small cell lung cancer (NSCLC) and might be related. The purpose was to investigate whether weight loss already starts early after initiation of CT‐RT and precedes radiation‐esophagitis. Materials and methods: In a retrospective cohort, weight and esophagitis grade ≥2 were assessed during the first weeks of (CT‐)RT in patients treated with concurrent ( n  = 102) or sequential ( n  = 92) therapy. In a prospective validation study, data on body weight, esophagitis grade ≥2, nutritional intake and muscle strength were obtained before, during and following CT‐RT. Results: In the retrospective cohort, early weight loss was observed in concurrently treated patients ( p  = 0.002), independent of esophagitis ≥ grade 2. Early weight loss was also observed in the prospective cohort ( p  = 0.003) and was not accompanied by decreases in nutritional intake. In addition lower limb muscle strength rapidly declined ( p  = 0.042). In the later weeks of treatment, further body weight loss occurred ( p  < 0.001) despite increased nutritional supplementation and body weight was only partly recovered after 4 weeks post CT‐RT ( p  = 0.003). Conclusions: Weight loss during concurrent CT‐RT for NSCLC starts early and prior to onset of esophagitis, re.uiring timely and intense nutritional rehabilitation. Electronic supplementary material: The online version of this article (doi:10.1007/s13539‐013‐0127‐5) contains supplementary material.